Polymer-fluorinated silica composite hollow fiber membranes for the recovery of biogas dissolved in anaerobic effluent - Wongchitphimon, Sunee (2018)
In this study, polymer-fluorinated silica composite hollow fiber membranes were fabricated and applied to a membrane contactor system for the recovery of methane dissolved in the anaerobic effluent. Such composite membranes allowed us to tailor the physical property such as porosity and mechanical strength and the surface hydrophobicity in separated processes. To develop the composite membranes, porous hollow fiber substrates were first fabricated with Matrimid®, a commercial polyimide. Subsequently, fluorinated silica particles were synthesized and anchored on the substrates via a strong covalent bonding. Due to the high porosity as well as the high hydrophobicity, our membrane showed an outstanding performance for the recovery of CH4 in the membrane contactor, such that the CH4 flux reached 2900 mg CH4/m2–h at the liquid velocity of 0.42 m/s at which the liquid phase still controlled the overall mass transfer. The composite membrane prepared in this work also showed a much better performance in the CH4 recovery than a commercial polypropylene membrane made for degasification of water. In addition, a long-term test with tap water saturated with the model biogas made up of 60:40 CH4/CO2 mixture demonstrated that our membrane can be stably operated for more than 300 h without experiencing pore wetting problem.